Pathogens in Maternal Blood and Fetal Cord Blood Using Q-Pcr Assay - Guang Qiong Hou; Sidney S. Chen; Chan Ping Lee (Elsevier, 2006)
Objective: To evaluate the rates of infection of asymptomatic fetuses and mothers through fetal cord blood and maternal blood examination results. Materials and Methods: Quantitative PCR (Q-PCR) was used to detect pathogens in maternal peripheral blood and fetal cord blood after delivery of term pregnancy at Buddhist Tzu Chi Medical Center, Hualien, between July 2002 and June 2003. Results: We used Q-PCR to detect pathogens in 29 samples of maternal blood. The maternal hepatitis B virus (HBV) DNA detection rate was 51.72% (15/29); for human cytomegalovirus DNA, the detection rate was 10.34% (3/29) and for Chlamydia trachomatis DNA the detection rate was 3.45% (1/29). No Neisseria gonorrhoeae DNA was detected. Whereas, in 29 samples of paired fetal cord blood, the detection rates were 27.59% (8/29), 10.34% (3/29), and 3.45% (1/29) for HBV DNA, C. trachomatis DNA, and N. gonorrhoeae DNA, respectively. No human cytomegalovirus DNA was detected in fetal cord blood. Conclusion: Our results revealed an unexpectedly high incidence of pathogens in fetal cord blood. Screening for the above pathogens in donor cord blood in cord blood banks using Q-PCR is strongly urged to decrease morbidity and mortality rates in fetal cord blood stem cell transplant recipients.